CLINICAL-LABORATORY EXAMINATION OF DENTAL DISEASES IN CHEMICAL INDUSTRY WORKERS (World Bulletin of Public Health, 2023)
The question of negative conditions in the oral cavity of workers in the chemical industry remains relevant. It has been proven that the high prevalence of noncarious lesions of the teeth and oral mucosa is associated with production processes such as oil and gas extraction, metallurgy, chemical production, baking and confectionery.
Keywords: dental diseases; general condition; caries